The Role of Perceived Usefulness on User Satisfaction of Regional Finance Information System - Utama, Sendy Cipta; Purnomosidhi, Bambang; Andayani, Wuryan (Jurnal Economia, 2017)
Abstract: The Role of Perceived Usefulness on User Satisfaction of Regional Finance Information System. This study aims to investigate empirically the influence of system quality, information quality, service quality and perceived usefulness on user satisfaction of the Regional Finance Information System. This study also examines the role of perceived usefulness on the effect of system quality, information quality, service quality on user satisfaction. Analysis technique using SEM (Structural Equation Modelling). Data were gathered from 147 staff of the finance management on all Regional Unit in Pemerintah Kota Batu. The samples selected by judgment sampling method. The findings show that the better of information quality and the higher of the user's perceived that the information systems were useful will increase user satisfaction. In addition, information quality will increase user trust on its support to decision making. Thus, will effect on the increase of user satisfaction. Keyword: System Quality, Information Quality, Service Quality, Perceived Usefulness, User SatisfactionAbstrak: Peran Mediasi Kegunaan Persepsian pada Kepuasan Pengguna Sistem Informasi Keuangan Daerah. Penelitian ini bertujuan untuk membuktikan secara empiris pengaruh kualitas sistem, kualitas informasi, kualitas layanan dan kegunaan persepsian terhadap kepuasan pengguna Sistem Informasi Keuangan Daerah (SIKD). Penelitian ini juga menguji peran mediasi kegunaan persepsian pada pengaruh kualitas sistem, kualitas informasi, kualitas layanan terhadap kepuasan pengguna SIKD. Teknik analisis menggunakan SEM (Structural Equation Modelling). Data didapatkan dari 147 staff pengelola keuangan daerah di seluruh Satuan Kerja Perangkat Daerah (SKPD) di Pemerintah Kota Batu. Sampel dipilih dengan metode judgment sampling. Hasil penelitian menunjukkan semakin baik kualitas informasi dan semakin tinggi kepercayaan pengguna bahwa sistem informasi bermanfaat akan meningkatkan kepuasan pengguna. Selanjutnya, Informasi yang berkualitas akan meningkatkan kepercayaan penggunanya bahwa informasi yang digunakan sebagai dasar pengambilan keputusan semakin baik sehingga berdampak pada meningkatnya kepuasan pengguna. Kata kunci: Kualitas Sistem, Kualitas Informasi, Kualitas Layanan, Kegunaan Persepsian, Kepuasan Pengguna